Lateral periaqueductal gray participate in the regulation of irritable bowel syndrome induced by chronic restraint stress - Jiaotao Xing; Ying Li; Jiali Hu; Liyao Gu; Guanghua Sun; Xiangle Li (Neurobiology of Disease)
Irritable bowel syndrome (IBS) is a functional bowel disorder defined by recurrent abdominal pain, coupled with irregular bowel habits and alterations in the frequency as well as the consistency of stool. At present, IBS is considered as a disease of gut-brain interaction, and an increasing number of studies are focusing on the brain-gut axis. However, the brain regions associated with IBS have not been fully studied yet. In this study, we utilized the chronic restraint stress (CRS) model to evoke IBS-like symptoms in mice, which were accompanied by anxiety-like behaviors and hyperalgesia. Through cFOS staining, we observed the activation of the lateral periaqueductal gray (LPAG) in the mice after CRS. By inhibiting the activity of the LPAG through tetanus toxin or chemogenetics, we found that IBS-like symptoms could be relieved, whereas chemogenetic activation of the LPAG induced IBS-like symptoms. Finally, we utilized the classic analgesic drug sufentanil and found that it could alleviate CRS-induced IBS-like symptoms.